Trace Fossils with Spreiten from the Late Ediacaran Nama Group, Namibia: Complex Feeding Patterns Five Million Years Before the Precambrian–Cambrian Boundary. (March 2014) - Macdonald, Francis A.; Pruss, Sara B.; Strauss, Justin V.
Abstract : Here we describe large, complex trace fossils in the late Ediacaran Omkyk Member of the Zaris Formation, Nama Group, southern Namibia. The horizontal trace fossils are preserved on a number of talus blocks from a bedding plane of a cm-thick sandstone lens from a single stratigraphic horizon less than 100 m below an ash bed dated at 547.3 ± 0.7 Ma. The forms consist of overlapping U-shaped spreiten elements with parallel limbs surrounded by an outer tube. Individual U-shaped elements are 0.2 to 1 cm in diameter, the outer tube is less than 3 mm in diameter, and the forms as a whole range from 5 to 30 cm long and 3 to 10 cm wide. The specimens commonly show a change in direction and change in diameter. The morphology of these trace fossils is comparable to backfill structures, particularly specimens of Paleozoic Zoophycos from shallow water environments. Here we interpret these horizontal spreiten-burrows to record the grazing of the trace-maker on or below a textured organic surface. The identification of large late Ediacaran trace fossils is consistent with recent reports of backfilled horizontal burrows below the Precambrian–Cambrian boundary and is suggestive of the appearance of complex feeding habits prior to the Cambrian trace fossil explosion.